Finite Element Analysis of Magneto-Rheological Damper - Kumar, Ashwani; Mangal, S. K. (Asian Journal of Engineering and Applied Technology, 2014)
In this paper, a finite element analysis of magnetorheological fluid (mr) damper is presented. It is necessary to develop a fem model for calculation of damping force of a given mr damper. An axi-symmetric fem model is thus built on ansys platform to analyze and examine a prototype of the mr damper. In this paper, geometrical parameters and magnetic flux density at the clearance space of the damper are studied. The study has indicated that the fem modeling is effectively portraying the behavior of a mr damper and is adequate enough for estimation of the damping force, its control and design. The results obtained in this paper will be helpful to the future designers to predict the damping force of a given damper.